PENGARUH PENGGUNAAN METODE DEMONSTRASI TERHADAP KONSENTRASI BELAJAR ANAK USIA 4-5 TAHUN DI TK ISLAM JASMIINA KECAMATAN TAPUNG KABUPATEN KAMPAR - Sholekhah Isniarum; Wusono Indarto; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aim is to know the effect of demonstration method to the child’s leaning Concentration at 4 – 5 Years in TK Islam Jasmiina Tapung District Kampar. The population is TK Islam JasmiinaTapung District Kampar by 15 children, the sample is 15 children. The method is experiment approach is a research that searches the effect of other variable in strong controls condition. The instrument is observation and documentation to note about all the activities in a year for the treatment. The data analysis technique by Scale Test and the statistic analysis by SPSS Windows ver. 22.Based on the hypothesis result there is the effect of the using demonstration method to the child’s learning concentration TK Islam JasminaTapung District Kampar. Obtain value t count of 5,297 with significance 0.000. T table values obtained with df 14 at significance level of 5% (two-tailed) of 1,761. Thus known t count (5,297)> t table (1,761) or significance (0.000) <5% (0.05). It can be known from The results of this study have percentages obtained pretest 61,11% and posttest 83,51%, the effect of demonstration method to the child’s leaning Concentration is 83,51% - 61,11% = 22,4%. Effect of demonstration method to the child’s leaning Concentration in the age of 4-5 years in early childhood Jasmiina Tapung District Kampar that is equal to 22,4 %.Keywords: Learning Concentration, Demonstration Method